Detection of Neisseria gonorrhoeae and Chlamydia trachomatis infections in pregnant women by multiplex recombinase polymerase amplification. - Jingjing Zhai (Public Library of Science (PLoS), 2021)
Chlamydia trachomatis (CT) and Neisseria gonorrhoeae (NG) are the main pathogenic microorganisms causing sexually transmitted infections. In this study, a multiplex thermostable recombinase polymerase amplification-lateral flow detection (RPA-LFD) assay was established, and the reaction conditions such as the ratio of primer concentration, magnesium ion concentration, amplification time and template DNA concentration in the multiplex RPA reaction were optimized. The optimized multiplex RPA-LFD method was used to detect both CT and NG positive control plasmids, and it was found that the LFD could be used to obtain visible results when the plasmid copy number was only 200. The sensitivity of the multiplex RPA-LFD method used for clinical samples was 85.62 (95% CI at 53.66-97.29) for NG detection and 90.90 (95% CI at 57.12-99.52) for CT detection.